Cyclooxygenase 1 (COX1) as an indicator of sperm quality in humans - Liu, Yongjie; Zhang, Fan; Dai, Liang (Andrologia, 2020)
Sperm quality is important for in vitro fertilisation and embryo transfer and intracytoplasmic sperm injection in the treatment of human infertility. The purpose of this study was to screen for biomarkers that could evaluate sperm quality. We analysed semen samples in 172 fertile males; multivariate logistic regression analysis showed that the levels of COX1 (17.5 ng/ml) in seminal plasma may represent a useful biomarker for sperm quality (area under the curve: 0.745; sensitivity: 0.808; specificity: 0.722). Analysis indicated that the values of parameters related to sperm quality changed significantly (p < .05) between COX1 level ≥ 17.5 ng/ml group and COX1 level < 17.5 ng/ml group. Further analysis of two consecutive semen samples (1‐hr interval) from 48 subjects revealed that the first semen samples (COX1 levels ≥ 17.5 ng/ml) had a higher sperm concentration and a larger proportion of spermatozoa showing progressive motility, a lower rate of sperm DNA fragmentation and a lower proportion of spermatozoa undergoing the acrosome reaction spontaneously (p < .05); identical results were observed for the second semen samples. These data indicated that COX1 could be used as an indicator for sperm status and may be helpful for identifying better quality spermatozoa for artificial insemination.